Ofelia Uribe de Acosta: Criticism of colombian education - Blanco, Vilma Nury (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
In June of 1963 the Colombian feminist Ofelia Uribe de Acosta published the book Una voz insurgente (an insurgent voice), where this book gave testimony to the social reality of Colombia and especially the women one between 1930 and 1963. Particularly, in the eighteenth chapter, the author presented her ideas about the Colombian education and she said that this had not progressed since the 19th century due to the management that the elite government gave the country. The rebellious spirit of Ofelia Uribe remained throughout the book against the paterfamilias that, according to her, it lost the moral quality of society rector and it did not respond to social, economic and political changes that appeared throughout the national territory. The article develops through primary sources. It focuses in the description of the life of Ofelia Uribe de Acosta, her critical thinking in front of the education in Colombia, in the light of the events of the time, and, a final reflection that collects the weaknesses of education related to education in the twenty-first century addressed by Ofelia Uribe de Acosta.